(untitled) (Bangladesh Journal of Animal Science, 2015)
An eight week feeding trial was carried out to compare the effect of antibiotic growth promoter (streptomycin) (AGP) and formic acid (FA) on growth and nutrient digestibility in broiler. A number of 150 day old (Hubbard strain) birds were allocated in 05 dietary groups viz. control, control with 0.02% AGP, control with 0.25% FA, control with 0.50% FA, control with 0.75% FA. Each group was replicated thrice having 10 birds and the birds were fed diet and water ad libitum for 8 weeks. Apparent digestibility of nutrients was determined at the end of the experiment. A significantly (p<0.05) reduced feed intake, improved feed: gain ratio and protein utilization were obtained for starter broilers fed 0.02% AGP, 0.5% FA and 0.75% FA. During finisher phase, AGP and 0.5% FA performed better in live weight, feed conversion ratio and protein utilization. Streptomycin and all the levels of FA resulted to better protein and ether extract digestibility. It may be suggested to use 0.50% FA in the diet of broilers in place of antibiotics. DOI: http://dx.doi.org/10.3329/bjas.v44i1.23146 Bang. J. Anim. Sci. 2014. 44 (1): 69-74